Everyday hero Machine Boy - Kniivila, Irma; Vuong, Tri (Skybound Comet, 2022)
Machine Boy tries to discover his origins from an obelisk that falls from outer space. But the object seems to be compromising his mission to help others on Earth. Includes discussion questions and a recipe.